P675 Real world evidence of tofacinitib in ulcerative colitis: short and long-term effectiveness, safety and impact of extraintestinal manifestations and immunomediated diseases. (30th January 2023) - Chaparro, M; Acosta, D; Rodríguez, C; Mesonero, F; Vicuña, M; Barreiro-de Acosta, M; Fernández-Clotet, A; Hernández Martínez, Á; Arroyo, M; Vera, I; Ruiz-Cerulla, A; Sicilia, B; et al.
Abstract: Background: Main aim: To assess the durability of tofacitinib treatment in patients with ulcerative colitis (UC). Secondary aims: To assess the short and long-term effectiveness; the tolerability of tofacitinib in clinical practice; and to evaluate the evolution of extraintestinal manifestations (EIMs) and immunomediated inflammatory diseases (IMIDs). Methods: Retrospective, multicenter study including UC patients who had received the first tofacitinib dose at least 8 weeks before the inclusion. Patients were followed-up from the first tofacitinib dose to treatment discontinuation or last visit, whichever came first. Only patients with active disease [Partial Mayo Score (PMS)>2] at tofacitinib start were considered in the effectiveness analysis. Clinical effectiveness was based on PMS. In patients who stopped tofacitinib before their last visit, the last observation carried forward method was used to impute missing values at subsequent time points. Results: 408 patients were included (figure 1). Incidence rate of tofacitinib discontinuation was 41% per patient-year of follow-up. The probability of maintaining tofacitinib is shown in figure 2a. Main reasons for tofacitinib withdrawal were primary non-response (44%) and loss of response (26%). Age at the start of tofacitinib (older) (HR=0.98, 95%CI=0.97-0.99) and the severity of clinical activity were associated with tofacitinib withdrawal (mild vs. remission: HR=1.5, 95%CI=0.5-4; and moderate-severe vs. remission: HR=3.0, 95%CI=1.2-7.4). Short-term effectiveness is shown in figure 3a. To have moderate-severe vs. mild disease activity at baseline (OR=0.2, 95%CI=0.1-0.4) and age at tofacitinib start (older) (OR=1.01, 95%CI=1.002-1.03) were associated with clinical remission at week 8. The probability of maintaining response in shown in figure 2b. Tofacitinib dose was escalated in 55 patients (66%) of those who had lost response, and 82% of them improved (60% regained remission). The proportion of patients on 10 mg b.i.d was over 40% in all timepoints during follow-up. The proportion of patients in clinical remission during follow-up in shown in figure 3b. Adverse events during tofacitinib treatment are summarized in figure 4. There was not any signal of negative impact of tofacitinib on EIM o IMIDs. Conclusion: Tofacitinib is effective in inducing remission even in highly refractory UC patients. A relevant proportion of patients discontinue the treatment, mostly due to primary failure. Dose escalation is effective to regain response after loss of efficacy. The safety profile is similar to that previously reported